2021
DOI: 10.1111/apt.16725
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: one‐year outcomes of gastric peroral endoscopic myotomy for refractory gastroparesis

Abstract: Background: Several studies have examined the efficacy of gastric peroral endoscopic myotomy (G-POEM) for gastroparesis.Aim: To evaluate the mid-term efficacy of G-POEM by meta-analysis of studies with a minimum 1 year of follow-up. Methods:We reviewed several databases from inception to 10 June 2021 to identify studies that evaluated the efficacy of G-POEM in refractory gastroparesis, and had at least 1 year of follow-up. Our outcomes of interest were clinical success at 1 year, adverse events, difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Long‐term efficacy beyond 12 months ranged from 53% to 70% of patients in retrospective studies, 75,77,91 and 33% to 56% in prospective trials, 89,92,93 based on GCSI variation. A recent meta‐analysis involving 10 studies and 482 patients calculated a pooled success rate of 61% at 1 year 94 . Longer‐term data were reported in a study by Tan, with a sustained efficacy in only 33% of patients at 2 years, whereas Ragi et al reported a sustained efficacy of 74% at 24 months 75 .…”
Section: Efficacy and Safety Of G‐poemmentioning
confidence: 99%
“…Long‐term efficacy beyond 12 months ranged from 53% to 70% of patients in retrospective studies, 75,77,91 and 33% to 56% in prospective trials, 89,92,93 based on GCSI variation. A recent meta‐analysis involving 10 studies and 482 patients calculated a pooled success rate of 61% at 1 year 94 . Longer‐term data were reported in a study by Tan, with a sustained efficacy in only 33% of patients at 2 years, whereas Ragi et al reported a sustained efficacy of 74% at 24 months 75 .…”
Section: Efficacy and Safety Of G‐poemmentioning
confidence: 99%
“…Gastric per-oral endoscopic myotomy (G-POEM) is an offshoot of POEM that permits endoscopic pyloromyotomy. The procedure was first described by Khashab et al in 2013 and >1,000 cases have been reported since then [ 56 ].…”
Section: Gastric Poemmentioning
confidence: 99%
“…Multiple observational studies have been published on G-POEM since its introduction into clinical practice in 2013. Kamal et al recently performed a systematic review and meta-analysis of 10 studies (482 patients) evaluating the efficacy of G-POEM in refractory gastroparesis with at least 1 year of follow-up [ 56 ]. The pooled rates (95% confidence interval) of clinical success at 1 year and adverse events were 61% (49%–71%) and 8% (6%–11%), respectively.…”
Section: Gastric Poemmentioning
confidence: 99%
“…[ 7 ] Similarly, Kamal et al showed reduction of GCSI by -1.4 (CI: -1.9 -0.9) at 1 year follow-up. [ 8 ] Neither of these meta-analyses compared G-POEM to surgical approach.…”
Section: Introductionmentioning
confidence: 99%